Changing fish trade practices in Myanmar’s rapidly transforming food system - Tezzo, Xavier; Bush, Simon R.; Belton, Ben; Oosterveer, Peter; Mon, Aung Hsu (Informa UK Limited, 2024)
Wholesale markets, wholesalers, and processors play critical but underappreciated roles in shaping food systems. Most conventional research on food provisioning analyzes value chains in terms of their structure, conduct, and performance. We contend that a practices lens can illuminate how food systems are produced and reproduced through the emergence of new wholesale practices relating to quality, trust, and risk, and provide more nuanced understandings of how markets and trading shape and are shaped by food system transformations. Applying a practices lens to the analysis of these changes can help identify new ways of steering food systems toward more sustainable outcomes.